Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Matrix-level co-occurrence metrics are sensitive to sampling grain: a case study in species-rich shrublands - G. L. W. Perry; Ben P. Miller; Byron B. Lamont; Neal J. Enright (Plant Ecology, 2020)

Winter climate variability in the southern Appalachian Mountains, 1910–2017 - Montana A. Eck; L. Baker Perry; Peter T. Soulé; Johnathan W. Sugg; Douglas K. Miller (International Journal of Climatology, 2019)
Located in the mid‐latitudes and exhibiting the greatest topographic relief in the eastern United States, the southern Appalachian Mountains (SAM) contain some of the most diverse climatological environments in the United States. This diversity is most pronounced in the winter season when temperature and snowfall can vary drastically across the region. In this study, we identify long‐term trends and variation of temperature and snowfall in the SAM of the southeastern United States during climatological winter (DJF) from 1910 to 2017. Along with recognizing statistically significant climatic trends, we also identify the influence of several teleconnection patterns, namely the El Niño‐Southern Oscillation (ENSO), North Atlantic Oscillation (NAO), and Pacific Decadal Oscillation (PDO) that further scientific understanding of how this region has remained a climatic anomaly. Results of this study indicate the SAM have experienced a statistically significant long‐term cooling trend since the early 20th century, with recent decades suggesting a reversal towards a warming pattern. Snowfall exhibited high interannual variability, with the 1960s and 1970s producing anomalously high amounts of snowfall. Several atmospheric forcing couplings are identified that align with anomalous conditions in the region. Most notably, negative temperature anomalies and higher snowfall amounts were frequently found during El Niño and negative NAO seasons, with the opposite being true during La Niña and positive NAO winters. The influence of these teleconnection patterns was spatially dependent, with lower elevations and eastern‐facing slopes being highly dependent on the phase of ENSO for snowfall, whereas higher elevations and western‐facing slopes were more reliant on the NAO. The identification of pattern couplings is critical to improving understanding of the anomalous climate of the SAM, enhancing seasonal forecasting, and predicting future climate change in the region.

Twenty years of ModelDB and beyond: building essential modeling tools for the future of neuroscience - Robert A. McDougal; Thomas M. Morse; Ted Carnevale; Luis Marenco; Rixin Wang; Michele Migliore; Perry L. Miller; Gordon M. Shepherd; Michael L. Hines (Journal of Computational Neuroscience, 2017)

Long-Term Trends of Nutrients and Phytoplankton in Chesapeake Bay - L. W. Harding; C. L. Gallegos; E. S. Perry; W. D. Miller; J. E. Adolf; M. E. Mallonee; H. W. Paerl (Estuaries and Coasts, 2016)

Scientific Bases for Numerical Chlorophyll Criteria in Chesapeake Bay - L. W. Harding; R. A. Batiuk; T. R. Fisher; C. L. Gallegos; T. C. Malone; W. D. Miller; M. R. Mulholland; H. W. Paerl; E. S. Perry; P. Tango (Estuaries and Coasts, 2014)

Low-dimensional trade-offs fail to explain richness and structure in species-rich plant communities - Alexandra Esther; Jürgen Groeneveld; Neal J. Enright; Ben P. Miller; Byron B. Lamont; George L. W. Perry; Britta Tietjen; Florian Jeltsch (Theoretical Ecology, 2011)

Green manure and phosphate rock effects on phosphorus availability in a northern Great Plains dryland organic cropping system - Terry L. Rick; Clain A. Jones; Richard E. Engel; Perry R. Miller (Organic Agriculture, 2011)

The NIF DISCO Framework: Facilitating Automated Integration of Neuroscience Content on the Web - Luis Marenco; Rixin Wang; Gordon M. Shepherd; Perry L. Miller (Neuroinformatics, 2010)

DNA-Protein Cross-Links in Erythrocytes of Freshwater Fish Exposed to Hexavalent Chromium or Divalent Nickel - Jim R. Kuykendall; Kyle L. Miller; Kristen M. Mellinger; Andrew J. Cain; Michael W. Perry; Michael Bradley; Eric J. Jarvi; Dennis J. Paustenbach (Archives of Environmental Contamination and Toxicology, 2009)

The NIF LinkOut Broker: A Web Resource to Facilitate Federated Data Integration using NCBI Identifiers - Luis Marenco; Giorgio A. Ascoli; Maryann E. Martone; Gordon M. Shepherd; Perry L. Miller (Neuroinformatics, 2008)

Federated Access to Heterogeneous Information Resources in the Neuroscience Information Framework (NIF) - Amarnath Gupta; William Bug; Luis Marenco; Xufei Qian; Christopher Condit; Arun Rangarajan; Hans Michael Müller; Perry L. Miller; Brian Sanders; Jeffrey S. Grethe; Vadim Astakhov; Gordon Shepherd; et al. (Neuroinformatics, 2008)

Issues in the Design of a Pilot Concept-Based Query Interface for the Neuroinformatics Information Framework - Luis Marenco; Yuli Li; Maryann E. Martone; Paul W. Sternberg; Gordon M. Shepherd; Perry L. Miller (Neuroinformatics, 2008)

The Neuroscience Information Framework: A Data and Knowledge Environment for Neuroscience - Daniel Gardner; Huda Akil; Giorgio A. Ascoli; Douglas M. Bowden; William Bug; Duncan E. Donohue; David H. Goldberg; Bernice Grafstein; Jeffrey S. Grethe; Amarnath Gupta; Maryam Halavi; David N. Kennedy; et al. (Neuroinformatics, 2008)

OdorMapComparer: An Application for Quantitative Analyses and Comparisons of fMRI Brain Odor Maps - Nian Liu; Fuqiang Xu; Perry L. Miller; Gordon M. Shepherd (Neuroinformatics, 2007)

A comparison of methods for the statistical analysis of spatial point patterns in plant ecology - George L. W. Perry; Ben P. Miller; Neal J. Enright (Plant Ecology, 2006)

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)